Leaky Dust Traps in Planet-embedded Protoplanetary Disks - Pinghui Huang; Fangyuan Yu; Eve J. Lee; Ruobing Dong; Xue-Ning Bai (The Astrophysical Journal, 2025)
From the survival of dust disks for a few Myr to the establishment of chemical dichotomy, dust traps are expected to play a pivotal role in sculpting protoplanetary disks and the early planet formation process. These traps may not be perfect, as evidenced by both numerical simulations and the observations of disks with gaps and cavities, inside which we detect some amounts of both gas and dust. Using two-fluid hydrodynamic global simulations in both 2D and 3D, we directly compute the dynamics of dust grains as they aerodynamically interact with the disk gas that is being perturbed by an embedded planet. In both 2D and 3D, we find the dust trap to be more leaky for a lower-mass planet and for a more turbulent disk. More crucially, we find that the fraction of dust mass that remains trapped within the pressure bump can be up to an order of magnitude more reduced in 3D compared to 2D, with all else being equal. Our simulations show a complex behavior of dust radial motion that is both azimuthally and poloidally nonuniform, with the overall dynamics dominated by the dust coupling to the gas flow even for Stokes number 0.1. The leaky traps we find suggest that the pebble isolation mass is likely not truly isolating and that gap-opening planets do not establish an unconditional impermeable barrier. Our findings have implications for recent JWST MINDS results, which show that volatiles, including water, are present in the inner regions of disks hosting outer dust rings.